History of ancient India - Tripathi, Rama Shankar (New Delhi : Motilal Banarsidass., 1942)
Contributed articles.
V. 1. Prehistoric roots -- v. 2. Protohistoric foundations -- v. 3. The texts, political history and administration, till c. 200 BC. -- v. 4. Political history and administration (c. 200 BC-AD 750) : from the end of the Mauryan rule to the beginning of the dominance of regional powers -- v. 5. Political history and administration (c. AD 750-1300) : regional powers and their interactions
Includes bibliographical references and indexes.
Keywords: India -- History -- 324 B.C.-1000 A.D.; India -- History -- To 324 B.C.; India -- History